At the Confluence of Public Policy and History: The Value of Historical Thinking in Public Policy Development - Soucier, Daniel (Maine Policy Review, 2019)
Daniel Soucier explains why conversations between those who study how policy decisions affected society in the past and those tasked with shaping the future are beneficial.
Keywords: historical analysis; policy formulation